Current mechanisms in obesity and tumor progression. Issue 6 (November 2020) - Fosam, Andin; Perry, Rachel J.
Abstract : Purpose of review: Hyperadiposity, as present in obesity, is a substantial threat to cancer risk and prognosis. Studies that have investigated the link between obesity and tumor progression have proposed several mechanistic frameworks, yet, these mechanisms are not fully defined. Further, a comprehensive understanding of how these various mechanisms may interact to create a dynamic disease state is lacking in the current literature. Recent findings: Recent work has begun to explore not only discrete mechanisms by which obesity may promote tumor growth (for instance, metabolic and growth factor functions of insulin; inflammatory cytokines; adipokines; and others), but also how these putative tumor-promoting factors may interact. Summary: This review will highlight the present understanding of obesity, as it relates to tumor development and progression. First, we will introduce the impact of obesity in cancer within the dynamic tumor microenvironment, which will serve as a theme to frame this review. The core of this review will discuss recently proposed mechanisms that implicate obesity in tumor progression, including chronic inflammation and the role of pro-inflammatory cytokines, adipokines, hormones, and genetic approaches. Furthermore, we intend to offer current insight in targeting adipose tissue during the development of cancer prevention and treatment strategies.